Content analysis of digital media coverage of the human papillomavirus vaccine school-entry requirement policy in Puerto Rico - Vivian Colón-López; Vilnery Rivera-Figueroa; Glizette O. Arroyo-Morales; Diana T. Medina-Laabes; Roxana Soto-Abreu; Manuel Rivera-Encarnación; Olga L. Díaz-Miranda; Ana P. Ortiz; Katelyn B. Wells; Coralia Vázquez-Otero; Pamela C. Hull (BMC, 2021)
Abstract Background In August 2018, Puerto Rico (PR) became the 4th state or territory in the United States to adopt a human papillomavirus (HPV) vaccine school-entry requirement, for students 11-12 years old. Evidence suggests that the content of media coverage may impact people's perception of HPV vaccine and their willingness to vaccinate. This study aimed to analyze the content of digital news coverage related to the implementation of the policy in PR. Methods A content review was conducted of digital media published from January 2017 through December 2018. The content reviewed was carried out in two steps: 1) creating a matrix to summarize each article's content about the policy and 2) qualitative analysis using a grounded theory approach. Results The search resulted in 34 articles obtained from 17 online local and international news outlets that reported the policy's implementation. Analyses showed that 61% of the news articles did not mention the number of required doses, and 79% discussed the new policy concerning cancer prevention. In 2017, news coverage focused mostly on describing the policy, while 2018 coverage focused on controversies surrounding the implementation. Neutral emergent codes included: 1) Description of the policy; 2) Information about HPV related cancers; and 3) General information about HPV vaccine. Negative emergent codes included: 1) infringement to patient and parental autonomy; 2) Hesitancy from the political sector, and 3) Hesitancy from groups and coalitions. Positive content included: 1) knowledge and acceptance of HPV vaccine for cancer prevention; 2) importance of education and protective sexual behaviors; and 3) new vaccination law proposal. Conclusions Most of the media coverage in PR was neutral and included limited information related to the vaccine, HPV, and HPV-related cancers. Neutral and negative themes could influence public concerns regarding the new policy, as well as HPV vaccination rates in PR.